Cycling under the influence of alcohol in Germany. - Huemer, Anja Katharina (Elsevier, 2018)
Cyclists have a relatively high risk of being injured in traffic accidents. In Germany, statistics have shown that cyclists injured in police-reported traffic accidents are often found to have cycled with high blood alcohol levels. Relevant research has discussed the ability of the Theory of Planned Behavior (Ajzen, 1991), deterrence factors, and habitual behavior to predict unsafe and rule-violating behavior in traffic. To promote safer cycling, the relative contributions of these predictors must be determined to design efficient countermeasures. In an online survey, N=353 participants reported cycling and drinking behaviors for 1 week and answered questions on the TPB, deterrence, and additional predictors. Perceived social norms were quite permissive and perceived behavioral control when cycling under the influence (CUI) of alcohol was quite high. Furthermore, a third of the cyclists reported CUI. Participants with experience of CUI reported having consumed large amounts of alcohol before cycling. High levels of cycling, a permissive attitude, and greater alcohol consumption per drinking episode predicted the number of CUI trips. The amount of alcohol consumed before one CUI trip was predicted by high perceived behavioral control when CUI, a high level of need for stimulation, and higher habitual alcohol consumption per drinking episode. Deterrence factors were found to have no influence on reported CUI. Overall, the findings suggested that Germans who habitually drink a large amount of alcohol are not deterred from CUI in the same manner that they would be from driving under the influence (DUI). The generally permissive perceived social norms did not differentiate between CUI and non-CUI cyclists, which indicated that a societal effort is required to balance the mismatch between CUI and DUI. In addition, changing the general drinking behaviors of highly educated Germans who cycle, would be beneficial for their health.
Keywords: Individualverkehr; Fahrradverkehr; Radfahrer; Risiko; Alkohol; Verkehrssicherheit; Verkehrsverhalten; Befragung; Fahrtüchtigkeit